Measuring quantum conductance and capacitance of graphene using impedance-derived capacitance spectroscopy - Lopes, Laís C. [UNESP]; Santos, Adriano [UNESP]; Bueno, Paulo R. [UNESP] (Elsevier, 2021)
Here, we demonstrate that impedance-derived capacitance spectroscopy is a useful method for measuring and analyzing the quantum of conductance and capacitance of a single-layer graphene sheet. Both quantum conductance and capacitance exhibit the expected traditional V-shape when measured as a function of bias potential (with the minima of both parameters being at the Dirac point) in a 1-Butyl-3-methylimidazolium tetrafluoroborate ionic liquid environment. Measurements were conducted at a specific low-frequency limit in which the conductance and capacitance were scanned as a function of bias potential to attain the quantum conductive and capacitive V-shapes. The V-shapes agree in terms of magnitude and profile with those reported in the literature using different methodologies and/or techniques. This validates impedance-derived capacitance spectroscopy as a suitable method to acquire key information of graphene and its derivatives. This method represents an alternative for rapid construction of both conductive and capacitive V-shapes of graphene in a single, simple experimental run.
Keywords: Graphene; Impedance spectroscopy; Nanoscale electrochemistry; Quantum capacitance; Quantum conductance